GENDER ANALYSIS ON SLANG LANGUAGE IN STUDENTS DAILY CONVERSATION - Kasmawati Amir; St. Azisah (ETERNAL (English, Teaching, Learning and Research Journal), 2017)
his research aimed at finding out the gender analysis on slang language used by the eight semester students of English Education Department in their daily conversation at UIN Alauddin Makassar. The researcher applied qualitative descriptive research. The participant of this research was the eight semester students of English Education Department at UIN Alauddin Makassar which consisted of 10 students. The participants were taken by using purposive sampling technique which consisted of 5 male students and also 5 female students. The data were collected through interviews and observations. The result of the data indicated that slang language used by the eight semester students of English Education Department in their daily conversation were slang in theater, art slang, public school or university slang as well as society slang. Besides, the male and female slang language was different caused of some factors such as situation and condition, age and politeness, as well as gender itself. There was a significant difference between male and female students’ percentage in using slang language. The mean score of male percentage in using slang language (66.48) while female only (33.50).Based on the finding and discussion of the research, the researcher drew a conclusion that male and female students of English Education Department used slang language in different way and also frequency.